FINANCIAL DISTRESS ANALYSIS WITH ALTMAN Z-SCORE APPROACH AND ZMIJEWSKI X-SCORE ON SHIPPING SERVICE COMPANY - Manalu, Sahala; Octavianus, Rony Joyo Negoro; Kalmadara, Galuh Safarina Sari (Jurnal Aplikasi Manajemen, 2017)
The purpose of this study is to analyze the financial distress condition of such service company by employing the method of Altman and Zmijewski as well as comparing the analysis result using both methods. This is a descriptive quantitative study with the sampling technique of purposive sampling. The number of samples of this study is 4 shipping service companies listed at Indonesian Stock Exchange since 2010, such as PT. SAMIN, PT. BLT, PT. MitrabahteraSegaraSejatiTbk (PT. MBSS) dan PT. Wintermar Offshore Marine Tbk (PT. WOM). The data are analyzed using Altman and Zmijewski method. The result indicates that out of four service companies: PT. MBSS is the most financially stable company, while PT. BLT is the company with the worst condition of financial distress condition. The use of both methods also produces results which are not different; what is different is only in terms of the assessment standards. It is advisable to predict financial distress in shipping companies using more than one method for every method employs different standard just to confirm the result.